Intrahousehold Allocation of Resources : The Bolivian Family - Inchauste, Gabriela (Washington, D.C. : International Monetary Fund, 2001)
Recognizing that intrahousehold inequalities exist, this study focuses on the distribution of resources toward children across household types. A bargaining framework is used to test whether it matters who has control over resources. Results show that control over resources matters, as well as the characteristics of family members. The policy implication is that the education of mothers is important to improve child welfare, over and above the benefits of cash transfer schemes. Parental education campaigns should accompany child welfare programs, particularly among indigenous families. Children fare better when mothers are educated, both parents are present, and there are fewer children.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet